2021
DOI: 10.21608/bjas.2021.189537
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Steroid Therapy on Growth hormone in Children with Nephrotic Syndrome

Abstract: Background: Nephrotic syndrome is the most frequent kidney-related condition in the United States today, providing a severe health risk. The cornerstone of therapy is still corticosteroids. Protein deficiency was a major cause of linear growth retardation in nephrotic individuals before steroids were administered. The goal of our research was to see how corticosteroids affected growth hormone in children with nephrotic syndrome. Methodologies: From February to December 2020, a cross-sectional research was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…Otherwise, there was no statistical difference in ocular manifestations between patients with frequent and infrequent relapses. Our results coincide with Abd Elhameed et al (12) who aimed how corticosteroids affected anthropometric measurements in kids with nephrotic syndrome, they found a statistically significant positive association between cumulative steroid dose and weight and a negative link between cumulative steroid dose and height. Williams et al (13) found that up to 80% of children with steroid sensitive nephrotic syndrome will experience at least one relapse, and more than half of these children will develop a frequent relapsing and/or steroid-dependent course, necessitating frequent exposure to corticosteroids and the side effects that come with it.…”
Section: Resultssupporting
confidence: 92%
“…Otherwise, there was no statistical difference in ocular manifestations between patients with frequent and infrequent relapses. Our results coincide with Abd Elhameed et al (12) who aimed how corticosteroids affected anthropometric measurements in kids with nephrotic syndrome, they found a statistically significant positive association between cumulative steroid dose and weight and a negative link between cumulative steroid dose and height. Williams et al (13) found that up to 80% of children with steroid sensitive nephrotic syndrome will experience at least one relapse, and more than half of these children will develop a frequent relapsing and/or steroid-dependent course, necessitating frequent exposure to corticosteroids and the side effects that come with it.…”
Section: Resultssupporting
confidence: 92%